Participatory development projects in the Andes - looking for empowerment with Q-Methodology - Zuger Caceres, Regula (International Maize and Wheat Improvement Center, 2005)
This is about the first steps in a study on poverty alleviation and the question whether participatory interventions make a significant contribution to the empowerment of poor Andean farmers. Participatory methods of intervention have been applied now for many years in many development projects, based on the philosophy that development will not be sustainable if the “end-users” of so called “beneficiaries” are not appropriately involved and participating in the projects. The process of active participation is supposed to empower the people involved and improve their personal development which at the same time is often considered to be as important for poverty alleviation as a good economic return of a development project. Q-Methodology is used in order to achieve better insight into the subjective nature of this famous factor “empowerment”, which is considered important even by the World Bank now. (Narayan D., 2002) The subjective reality of a person is a functional reality, it is often much more functional than the external “objective” reality, because it is what people perceive and what makes up their life. With Q-Methodology people can be grouped into “factors” (groups of people) with different functional realities, with different perceptions of “reality”, with different reactions within certain situations. The thesis is that if people get “empowered” by an intervention of a project, at least their inner, subjective reality is supposed to change, even if their external reality might not change substantially yet. Therefore people in several different places in the Peruvian Andes are assessed with Q-Methodology before and after intervention of two different types of projects and changes shall be tracked. At this stage there only exist the data “before-intervention”, the interviews “after-intervention” will take place next. The projects mentioned are FAO Farmer Field Schools near Huancayo, central part of Peru and the Rural Sanitation Program SANBASUR near Cusco, more in the South of Peru. In Huancayo the study includes 88 persons, 51 project participants and 37 test persons (non participants); in Cusco the study is including 77 project participants and 77 nonparticipants. First analyses of the baseline data are on the way.